Gaya Hidup Hedonisme Mahasiswa Pascasarjana di Media Sosial - Mufidah, Elia Firda; Wulansari, Peppy Sisca Dwi (JKI (Jurnal Konseling Indonesia), 2018)
Graduate students are in early adulthood at the age of 18 to 40 years. As adolescence moves into adulthood, adulthood (emerging adulthood) is marked by experimentation and exploration. Hedon lifestyle can not be separated from the world of students. Students tend to have a hedon lifestyle in order not to be labeled obsolete or old age kids. This research uses qualitative research with case study type with research subject of guidance and counseling students of State University of Malang class of 2016. The conclusion shows that graduate student has a hedonism lifestyle is done to get pleasure so that encourage them to complete their duty.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">